Model Pengelolaan Pesantren Mahasiswa Fakultas Ilmu Tarbiyah dan Keguruan IAIN Surakarta - Khuriyah Khuriyah; Noor Alwiyah (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2016)
To set up a boarding school student (PESMA) required a management model that can be used as guidelines in managing Pesma in FITK IAIN Surakarta. The purpose of this study is to produce a management model pesantren students with appropriate characteristics and can be implemented in FITK IAIN Surakarta.This study employed  Research and Development, carried out in an environment FITK IAIN Surakarta of the month from May to July 2015. Data obtained came from dean, vice of dean, student representative, expert evaluation and boarding. The data were collected through questionnaires, documentation, and interviews. Data were taken from the questionnaires were analyzed with SPSS 17. The results showed that the model of management of boarding students in FITK IAIN Surakarta consisted of the following characteristics: 1) the model of management of Pesantren Mahasiswa generated through four stages of development steps are: a) planning, b) develope preliminary form of product, c) preliminary field testing, d) the final product revision; 2) the instruments of boarding school management of students have high validity and reliability.Keywords: management model, student boarding school